A feasibility study of UniqCare in Quezon City - Julongbayan, Paul John; Urbiztondo, Jacky; Tabia, Andrew Mark; Lagria, Raymond Freth (Quezon City College of Engineering, University of the Philippines Diliman, 2010)
Issues regarding contraceptives, the Reproductive Health Bill, sex education to be taught in schools, reproductive health care, population controi and many others are prominent at these times over the country. The government had become aggressive in tackling these issues and many are opposing them, however, not as many as who are with them. With these issues around, the UniqCare organization wants to promote and help the government through providing reproductive health care services to less accessible areas by the government. UniqCare's mission is to promote its advocacy of promoting the reproductive health care. As initialized, UniqCare will operate first in five centers around Quezon City, the representative of Metro Manila. Then, as these five centers operate, it wiii go on campaigns and advertisements to highlight the organization's mission. A feasibility study was conducted to test the centers' feasibility. The market feasibility showed that there are a total of around 292,000 pieces of contraceptives to be sold in five years. This includes all types of contraceptives provided by the centers. Since the centers are designed to be lying-in clinics, maternal and birth services are also available. The demand for the birth deliveries is 44 births per year at least for the five centers to be located. The total projected revenues for both of the contraceptives to sell and for the birth deliveries sums up to around 21 million pesos in five years. The proponents then tested UniqCare's technical feasibility. The study revealed that the five centers will be located in the top five populated barangays in Quezon City namely, Batasan Hills, Payatas, Holy Spirit, and Pasong Tamo. These areas will house one UniqCare center each. Each UniqCare center will be manned by 3 personnel, the midwife, the assistant and the utility. UniqCare services especially the birth deliveries are 24-hours available so there is a need for another personnel manning the centers during the night. Also, UniqCare must be partnered with the nearest Hospital for referrals if services in the centers cannot be carried out. UniqCare then tested financial feasibility ratios for the monetary aspect of UniqCare. The study showed that a positive IRR of 57.96% will be realized in five years and a 1.606 years will be the payback period of the business. Since UniqCare's advocacy is to promote the reproductive health care in less accessible areas, then it is also evident that there is a great push in helping the country's social and economic state. This leads to helping the people to have healthy lives. In conclusion, UniqCare, with all the feasibility studies conducted, with the market demand positive, with the technicalities of the centers possible, and with the financial and socio-profitability positive, then the UniqCare, reproductive health care provider, is indeed feasible.
Submitted in partial fulfillment of the course requirements in IE 153 : Project development and management.
Keywords: Reproductive health services -- Philippines; Feasibility studies